Chinese Immigrants’ Health Beliefs and Practices of Traditional Chinese Medicine in British Columbia of Canada - Tina Wu (Chinese Medicine and Culture)
Objective:. This study is to address the health beliefs and health behavior of Chinese immigrants residing in the Greater Vancouver area of British Columbia (BC) Province in Canada. This article discussed Chinese immigrants’ traditional Chinese medicine (TCM) use, health beliefs, and health behaviors. Methods:. Information used in this study is based on data collected in the Chinese-speaking community in the Greater Vancouver area of BC in 2020–2022. Quantitative and qualitative methods were applied to this study. The first stage recruited 314 participants for the quantitative study to cross-validate an instrument tool, followed by the 2nd stage of 20 stratified random sampling out of the 314 participants for TCM-related in-depth qualitative interviews. This study focuses on the second stage of TCM qualitative interviews. Results:. Results indicated that TCM health beliefs have cultural and spiritual meanings tied to the Chinese-speaking participants. There are barriers for the Chinese-speaking population to access the existing healthcare services due to their TCM health beliefs and other health needs, for example, family doctors, integrated medicine for better health outcomes, and mental health services especially during the coronavirus disease 2019 (COVID-19) pandemic. Conclusion:. Integrating TCM health beliefs and behaviors of Chinese-speaking immigrants into existing Canadian mainstream health services are strongly recommended.